PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) SISWA KELAS V SDN 003 SUNGAI MANASIB - Suraidah Suraidah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of problem in this research was students less of active in learning process. Students inclined relax in receive the lesson. Students less motivation in science lesson. In learning process, the cooperative learning process make a match type students have more motivation study in a group. There are finding a couple while study about one concept or topic in happy situation. In other that to practice carefulness, accuracy, coincidentally and also velocity with the result students more active in learning process. This was a classroom action research which the subjects or research was students grade V in elementary school 003 sungai manasib about magnet force subject 2014/2015 academic year. The research was aimed to increase students’ achievement in science lesson for students grade V elementary school 003 sungai manasib by using cooperative learning make a match type. Based on the result of analysis data, the research shown that before and after did the action students’ achievement was rise. Before the action did, in daily examination was 64,8 increase in the first cycle test as 4,4 points (67,90%). In the second cycle, students; achievement increase 12,8 points. Teacher’s activity in the first cycle was 77,1 % categorized as good increase to 93,7 % with increase percentage as 16,4 % and second cycle as very good. Students’ activity also increased in the first cycle 65,2% categorized as good and increase to 80,5 % in the second cycle with increase percentage was 15,6 %. Based on explanation above it can conclude that using implementation of cooperative learning make a match to increase students’ achievement in science lesson for students grade V elementary school 003 Sungai Manasib.Keywords : Cooperative Learning Type, Students’ Achievement in Science Lesson.